The Effect of Problem Based Learning Model with STEAM Approach on Mathematical Critical Thinking Ability - Siti Nurkhalizah; Cecep Anwar Hadi Firdos Santosa (FKIP Universitas Mataram, 2025)
This study aims to determine the effect of the problem-based learning model with the STEAM approach on students' critical thinking skills and their response to the model. Using a quantitative method with a quasi-experimental design, this study involved ninth-grade students with similar academic characteristics from a junior high school in Serang City. The sample consisted of 72 students from two classes: IX E as the experimental class that applied PBL-STEAM and IX A as the control class that used the collaborative model. The results showed that 1) students' critical thinking skills with the PBL-STEAM model were better than students who applied the collaborative model based on the experimental class posttest results with an average value of 83.33, superior to the control class, which was only 78.19. 2) Analysis of student response questionnaires showed that the application of the PBL-STEAM model received a positive response and was able to increase student knowledge of the material taught. 3) The PBL-STEAM model is effective in improving students' critical thinking skills so that it becomes one of the alternative learning models that can be applied by teachers in learning mathematics.